Supervisi, Penjaminan Mutu, dan Manajemen Kelas Yang Kondusif Untuk Kesuksesan Kualitas Pembelajaran - Raharja, Reza Mauldy; Asrul, Asrul; Imron, Ali; Sunarni, Sunarni (UHN IGB Sugriwa Denpasar, 2023)
The focus of the discussion in this paper is the concept of classroom management supervision and quality assurance. Supervision is an action carried out by leaders in schools that emphasize coaching and development activities for the person being supervised. The quality of education in general starts from the quality of educators and the implementation of education in the classroom. Implementation of education in practice occurs in the classroom where the class is the smallest element in the implementation of education and learning in educational institutions. Teachers are the spearhead of implementing the educational process in the classroom, also play a role as professional educators and have very complex tasks, not limited to learning activities, including administrators, evaluators, counselors, and so on. Teachers in carrying out their daily tasks have a very large role. Their commitment and professionalism are highly expected in efforts to guarantee the quality of education. Class management activities are also activities that cannot be underestimated among the many tasks of teachers, teacher skills in managing classes are an added value that must be owned by professional teachers because as a vital element in the implementation of education, it is appropriate for classes to be managed and managed so that they are of high quality with the help of the school principal. as a supervisor at school. Therefore, a school principal needs to guide, foster and properly direct his teachers and staff. Keywords: Supervision, Quality Assurance, Classroom Management